2016
DOI: 10.1002/elps.201600090
|View full text |Cite
|
Sign up to set email alerts
|

A CIEF‐LIF method for simultaneous analysis of multiple protein kinases and screening of inhibitors

Abstract: Here, a CIEF‐LIF method for multiple protein kinase simultaneous analysis and inhibitors throughput screening with fast rate and low cost is presented. Comparing with CZE, CIEF‐LIF exhibited great focusing ability and high separation efficiency for substrate and phosphorylated peptides, and is applicable for multiple kinases simultaneous analysis regardless of their substrate peptides compositions and charge statuses. Thus, highly sensitive analysis for cyclic adenosine 3’, 5’‐monophosphate‐dependent protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In a similar work, cIEF-LIF was compared to CZE for its ability to simultaneously study composition and inhibition of multiple protein kinases. 89 The method was successful regardless of structure and charge of the substrate peptides. The use of nanogels to physically constrain an enzyme in a separation capillary while performing electrophoretically mediated microanalysis (EMMA) was proposed for improving sensitivity and separation specificity.…”
Section: Applicationsmentioning
confidence: 95%
“…In a similar work, cIEF-LIF was compared to CZE for its ability to simultaneously study composition and inhibition of multiple protein kinases. 89 The method was successful regardless of structure and charge of the substrate peptides. The use of nanogels to physically constrain an enzyme in a separation capillary while performing electrophoretically mediated microanalysis (EMMA) was proposed for improving sensitivity and separation specificity.…”
Section: Applicationsmentioning
confidence: 95%
“…Online enzyme assay integrates together enzyme incubation, reaction, and product detection in a single capillary within one run. Comparing off‐line enzyme assay, it thus greatly simplified enzyme assay process, and has developed two mainly operation modes, at inlet and electrophoretically mediated microanalysis (EMMA) .…”
Section: Online Screening Of Enzyme Inhibitorsmentioning
confidence: 99%
“…The use of CE and ME in clinical protein analysis has not shown the expected growth that was expected. There have been some advances in the types of detectors used such as CL , LIF , LED‐LIF , and MS . An interesting study on protein analysis in the vitreous humor of the eye was reported by Reich et al.…”
Section: Applications In Different Clinical Fieldsmentioning
confidence: 99%